Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fphys.2018.01517
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmic Remodeling of Calcium Homeostasis in Cardiac Disease; Implications for Diabetes and Obesity

Abstract: A rapid growth in the incidence of diabetes and obesity has transpired to a major heath issue and economic burden in the postindustrial world, with more than 29 million patients affected in the United States alone. Cardiovascular defects have been established as the leading cause of mortality and morbidity of diabetic patients. Over the last decade, significant progress has been made in delineating mechanisms responsible for the diminished cardiac contractile function and enhanced propensity for malignant card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 306 publications
(351 reference statements)
3
33
0
Order By: Relevance
“…However, during stress, hyperactivity of RyR2s has been associated with SCWs, which could translate into disturbances in membrane potential, i.e., delayed or early after depolarizations leading to malignant arrhythmias and sudden cardiac death (Belevych et al, 2012). Posttranslational modifications of the channel, including phosphorylation by PKA and/or CaMKII and oxidation of reactive cysteines, have been implicated in the RyR2 hyperactivity characteristic of cardiac disease and aging (Belevych et al, 2012; Zima et al, 2014; Hamilton and Terentyev, 2018, 2019). Consistent with this, treatment with ROS scavengers stabilized aberrant Ca 2+ release and lessened triggers for arrhythmia in conditions accompanied by oxidative stress, including heart failure (Terentyev et al, 2008) and myocardial infarction (Belevych et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, during stress, hyperactivity of RyR2s has been associated with SCWs, which could translate into disturbances in membrane potential, i.e., delayed or early after depolarizations leading to malignant arrhythmias and sudden cardiac death (Belevych et al, 2012). Posttranslational modifications of the channel, including phosphorylation by PKA and/or CaMKII and oxidation of reactive cysteines, have been implicated in the RyR2 hyperactivity characteristic of cardiac disease and aging (Belevych et al, 2012; Zima et al, 2014; Hamilton and Terentyev, 2018, 2019). Consistent with this, treatment with ROS scavengers stabilized aberrant Ca 2+ release and lessened triggers for arrhythmia in conditions accompanied by oxidative stress, including heart failure (Terentyev et al, 2008) and myocardial infarction (Belevych et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic enhancement of mitochondrial antioxidant activity via overexpression of catalase reduced oxidative modifications and attenuated age-related changes in excitation-contraction coupling protein expression [139,140]. Electron and ROS scavenging or inhibition of mitochondrial oxidase has been shown to improve intracellular Ca 2+ handling and reduce arrhythmic potential in other disease models as well as aging, including heart failure and diabetic cardiomyopathy [9,12,45,141,142].…”
Section: Intracellular Ca2+ Homeostasis In the Aged Heartmentioning
confidence: 99%
“…We and others have comprehensively reviewed the function, post-translational modifications, and role of excitation-contraction coupling proteins in the development of cardiac arrhythmia [12,13,14,15,16]. In this case, we provide a more concentrated focus on aberrant intracellular Ca 2+ release and mechanisms of arrhythmogenesis that occur in the aged heart.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoplasmic reticulum Ca 2+ leak-induced changes in intracellular ROS, [Ca 2+ ] m and ΔΨ m may produce secondary effects on other key components of intracellular Ca 2+ handling machinery including SERCa2a, Na + /Ca 2+ exchanger and L-type Ca 2+ channels [8,33,68]. In the present study, we did not measure changes in activities of these complexes in caffeine-treated rat VMs or CPVT mouse VMs, nor did we measure intracellular [ATP].…”
Section: Limitationsmentioning
confidence: 75%
“…Parallel changes in RyR2 activity and mito-ROS production are hallmark features in cardiac pathology such as HF, MI, aging, or diabetic-induced cardiomyopathy [4,18,22,33,34,36,64,70]. We recently demonstrated that modulation of mito-Ca 2+ efficiently regulates RyR2 activity via mito-ROS [32].…”
Section: Discussionmentioning
confidence: 99%